The effect of using Herbicides on the growth and yield varieties of wheat (Triticum aestivum L.) and accompanying weeds. - Almashhadany, Ahmed (Eastern Journal of Agricultural and Biological Sciences, 2024)
A field experiment conducted during the winter agricultural season 2021-2022 in the fields of farmers in Nineveh Governorate Mosul district, in Yaramjah location. The experiment had couple factors, first one was two bread-wheat cultivars (Al-Arabia, Bora, Pisanzo and Tal-Afar3). another factor was three chemical herbicides (Atlantis, Suraj, Limitless) specialized in controlling weeds accompanying wheat crops. In the current experiment, a design (RCBD) with a split-plot, with three replications, and using of the SAS “statistical analysis system” in analyzing data. The results obtained from this research were as follows: Limitless Herbicide showed the lowest [number, and dry weight] weeds, with a control efficiency of 51.47%, and 51.89% respectively. In trait of spikes number, the cultivar (Pisanzo) was superior, with a record of 428.4 spikes.m-2. In grain yield; the (Pisanzo) cultivar had significantly superior, it was recording 600.5 g.m-2.